Evaluation of nutritional status and related factors in children with cystic fibrosis - Yücel, Aylin; Pekcan, Sevgi; Eklioğlu, Beray Selver; Yüksekkaya, Hasan Ali; Ünal, Gökçen; Yılmaz, Aslı İmran (The Turkish Journal of Pediatrics, 2022)
Background. This study aimed to evaluate the nutritional status and body composition in children with cystic fibrosis (CF), in accordance with the new nutritional targets defined by European Society for Clinical Nutrition and Metabolism (ESPEN), the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and the European Cystic Fibrosis Society (ECFS) 2016. Methods. In this cross-sectional study, data were collected prospectively in a single centre. A record was made for a total of 95 patients with CF of clinical data. Anthropometric data were evaluated using the World Health Organization growth standards. The bone mineral density (BMD) z-score was adjusted for height by measuring dual-energy X-ray absorptiometry (DXA). The speed of sound z-score values were measured with quantitative ultrasound (QUS). Results. The nutritional status was normal in 37.9% of patients aged < 2 years and 33.3% of patients aged 2-18 years. When the DXA BMD z-score values were corrected for height, it was determined that the BMD deficit was less. The calcaneus QUS SOS z-score mean value was lower than the mean height for age z-score adjusted BMD (BMDHAZ). Conclusions. The malnutrition rates of CF patients were higher than the rates previously reported in literature. As there are insufficient nutritional data in Turkey, there is a need for multi-centre studies to determine the frequency of malnutrition according to the new classifications. It is clear that QUS measurements cannot replace DXA in the diagnosis of osteopenic bone disease. However, when low values are determined with QUS as the first recommended measurement in the screening of bone status, it can be considered appropriate to confirm the status with DXA.
Keywords: bone densitometry; cystic fibrosis; height for age z-score adjusted BMD; malnutrition; nutritional status; quantitative ultrasound